Fluoroscopic and Endoscopic Gastrostomy Tube Placement: Regional Variation and Their Prevalence - Khalid, Syed I.; Wu, Rita; Gazal, Ayoolamide; Tasse, Jordan C.; Tabriz, David M.; Madassery, Sreekumar; Turba, Ulku C.; Arslan, Bulent (Journal of Clinical Interventional Radiology ISVIR, 2019)
Objective This study aims to assess the regional variation and overall longitudinal prevalence of approaches to gastrostomy tube placement in patients covered by Medicare or Medicaid.Background Gastrostomy tubes are most commonly inserted endoscopically given the approaches’ demonstrated safety, success, and patient outcomes as compared with laparoscopic approaches. Recently, the growth of interventional radiology services has provided patients with an alternative percutaneous approach. The safety and efficacy of this approach as opposed to endoscopic approaches has yet to be determined.Methods From 2005 to 2014, Medicare Standard Analytic Files derived from Medicare parts A and B, which contain 100% of inpatient and outpatient facility records billed to Medicare, were retrospectively analyzed. Age, sex, year of placement, region, comparative quarterly ratio, regional cost variation, and overall financial cost were compared between both cohorts.Results Our population included a total of 336,021 patients; of those, 30,327 patients underwent fluoroscopic guided procedures, and 305,694 patients underwent endoscopic procedures. Age (p < 0.001), region (p = 0.043), and year of placement (p < 0.001) varied significantly between these populations. Fluoroscopic-guided procedures were found to have a statistically significantly lower average cost of treatment compared with endoscopic gastrostomies ($2,018.62 vs. $2,471.33, respectively, p = 0.03).Conclusion This study demonstrates an increasing prevalence of fluoroscopically placed gastrostomy tubes as compared with those placed endoscopically.
Keywords: gastrostomy; G-tube; percutaneous endoscopic gastrostomy; endoscopic; fluoroscopic